Development of Children's Literature Reading Materials to Support SDN 028228 Binjai Student Literacy Activities - Meta Melisa Br Ginting; Mutsyuhito Solin; Wisman Hadi (Britain International for Academic Research (BIAR) Publisher, 2021)
This research is motivated by the lack of availability of reading materials for children's literature, reading materials that are not suitable for the age of growth and development of children's psychology, then students have an interest in reading, and reading habits are not yet entrenched, so it is necessary to develop varied reading materials and support students in activities. literacy. Children's literature reading materials are needed at SDN 028228 Binjai to support students' literacy activities. This study aims to determine the results of the development of children's literature reading materials in the form of comics to support literacy activities of SDN 028228 Binjai students. The research method used was research and development (Research and Development) by Borg and Gall. The results showed that (1) The reading material development process was carried out in several stages, namely preliminary studies, initial product development and product testing. (2) The results of the reading material feasibility test show that (a) the result of the material expert's validation on the reading material as a whole is 83.3% with the criteria of